The different faces of mental illness stigma: Systematic variation of stereotypes, prejudice and discrimination by type of illness. Issue 5 (30th May 2022) - Görzig, Anke; Ryan, Lauren Nicole
Abstract : Mental illness (MI) stigma has been characterized as multi‐dimensional including problems of knowledge (stereotypes), attitudes (prejudice) and behavior (discrimination); however, most research practice is predominantly applying unidimensional behavioral measures such as social distance scales. Moreover, specific types of MIs and different forms of discriminatory behaviors are not being differentiated. The Stereotype Content Model predicts that group stereotypes (warmth, competence) are linked with different forms of discriminatory behaviors (harm or facilitation) via emotional prejudices (pity, envy, contempt). The present study sought to establish how differential stereotypic perceptions of MI subgroups elicit distinct forms of behavioral discrimination via emotional prejudices. A community sample ( N  = 60) was randomly assigned to one of three conditions representing MIs across the warmth‐competence stereotype space. Patterns of self‐completed measures for stereotypes, emotions and behaviors differed significantly between conditions. The association between stereotypes and behaviors were largely mediated by emotions. Systematic patterns of stereotypic perceptions, emotional prejudices and behavioral discrimination are present for individuals with different types of MIs. Hence, generic measures of discrimination, such as social distance scales, may be misleading. Intervention strategies should consider the systematic variation of the factors involved in stigma, differentiating by type of MI and discriminatory behaviors.